Communication implications of workers' perceptions in the manufacturing industry regarding condom use - Jordaan, Christina (University of the Free State, 2004)
The regular use of condoms is one of the most effective ways to prevent infection with HIV. The efficacy of the condom as instrument to combat infection is, however, negatively impacted upon by popular (mis)perceptions. This leads to incorrect use of, or the refusal to use, condoms. Agencies seeking to promote condom use should therefore utilise these perceptions in their communication strategy designs. This article explores perceptions on condom use in a sample group of 20 persons who attended a three-day training workshop on HIV/AIDS prevention in Johannesburg from 29 September to 1 October 2003. The group was constituted of workers in the manufacturing industry who had been selected by their management and peers because they were deemed to have the potential to be trained as peer educators in HIV/AIDS prevention.
Keywords: Condoms; HIV and AIDS; Communication strategy; Manufacturing industry